Development of mobile application for cervical cancer screening in women: Protocol of a multi-phase study - Marzieh Ghasemi-Gujani; Mitra Savabi-Esfahani; Mahnaz Noroozi; Mohammad Satari (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Cervical cancer is one of the most common cancers in women. It is considered preventable due to the possibility of screening. The common barriers to cervical cancer screening include lack of knowledge, lack of time, and wrong beliefs. The use of e-Health technologies is one of the approaches for health promotion. The present study is aimed to the development of a mobile application for cervical cancer screening in women. MATERIALS AND METHOD: This is a multi-phase study. In the first step, a literature review will be conducted to examine factors related to cervical cancer screening and existing applications related to cervical cancer and its screening. Then, in the second step, a cross-sectional study will be conducted to investigate the factors related to cervical cancer screening in 246 women referred to comprehensive health centers and women's clinics in teaching hospitals in Isfahan, Iran. The comprehensive health centers and women's clinics in teaching hospitals will be randomly selected using a lottery method. Using convenience sampling, women who meet the inclusion criteria will be included in the study, provided they provide informed consent. The data will be collected using a questionnaire, and then the descriptive and inferential statistical tests and SPSS18 software will be used to analyze the data. In the third step, specialists (gynecologists, reproductive health specialists, and midwives) will prioritize the application content by filling out a questionnaire. Then, the research team will compile the application content draft, and this draft will be reviewed and approved by experts on the expert panel. The prototype of the application will be prepared, and experts will evaluate it in the fifth step. DISCUSSION: The results of this study will result in the development of applications for cervical cancer screening. The use of mobile applications can be useful in lifting some of the barriers to screening. Therefore, developing such applications may help improve cervical cancer screening.